Влияние ветровой эрозии на окружающую среду и человека в условиях радиоактивного загрязнения западного полесья Украины - Голуб, Валентина Олександрівна; Голуб, Сергій Миколайович; Голуб, Геннадій Сергійович; Holub, Valentyna O.; Holub, Serhii M.; Holub, Hennadii S. (Российский университет дружбы народов, 2015)
The experiment showed that the best effect in the protection of soddy podsolic soil with contamination density of 1,5 Cu/cm2 from wind erosion and in the reduction on accumulation raidionuclides in fields crops has chisel tillage.
Effects of wind erosion on the environment and human in the radioactive contamination of the western Polesye of Ukraine
Keywords: транслокации радионуклидов; ветроэрозионные процессы; разноглубинная отвальная вспашка; поверхностная дисковая обработка; чизельная обработка; плоскорезная обработка; севооборот; удельная активность